Heteroatom Tuning of Bimolecular Criegee Reactions and Its Implications. Issue 43 (28th September 2016) - Kumar, Manoj; Francisco, Joseph S.
Abstract: High‐level quantum‐chemical calculations have been performed to understand the key reactivity determinants of bimolecular reactions of Criegee intermediates and H2 X (X=O, S, Se, and Te). Criegee intermediates are implicated as key intermediates in atmospheric, synthetic organic, and enzymatic chemistry. Generally, it is believed that the nature and location of substituents at the carbon of the Criegee intermediate play a key role in determing the reactivity. However, the present work suggests that it is not only the substitution of the Criegee intermediate, but the nature of the heteroatom in H2 X that also plays a crucial role in determining the reactivity of the interaction between the Criegee intermediate and H2 X. The barriers for the reactions of Criegee intermediates and H2 X satisfy an inverse correlation with the bond strength of X−H in H2 X, and a direct correlation with the first p K a of H2 X. This heteroatom tuning causes a substantial barrier lowering of 8–11 kcal mol −1 in the Criegee reaction barrier in going from H2 O to H2 Te. An important implication of these results is that the reaction of the Criegee intermediate and H2 S could be a source of thioaldehydes, which are important in plantery atmospheres and synthetic organic chemistry. By performing the reaction of Criegee intermediates and H2 S under water or acid catalysis, thioladehydes could be detected in a hydrogen‐bonded complexed state, which is significantly more stable than their uncomplexed form. As a result, simpler aliphatic thioaldehydes could be selectively synthesized in the laboratory, which, otherwise, has been a significant synthetic challenge because of their ability to oligomerize. Abstract : Gas‐phase reactions : The calculated barriers for the bimolecular reactions of Criegee intermediates and H2 X inversely correlate with the bond strength of the X−H bond of H2 X or directly correlate with the first p K a value of H2 X. Thus, it is not only the substitutions of Criegee intermediates but also the properties of the heteroatom in H2 X that play a crucial role in determining the reactivity.